2016
DOI: 10.1186/s13256-016-0988-2
|View full text |Cite
|
Sign up to set email alerts
|

Deletion 21q22.3 and duplication 7q35q36.3 in a Colombian girl: a case report

Abstract: BackgroundGenetic disorders are a major cause in the etiology of cases with intellectual disability; however, analysis by a conventional technique such as cytogenetic karyotyping only allows the detection of chromosomal alterations in approximately 9.5 % of cases. The inclusion of new technologies such as high resolution microarray analysis has allowed the study of alterations in chromosomal segments that are less than 5 Mb in length; this has led to an increase in the diagnosis of these patients of up to 25 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…Ciocca et al [20] reported a syndromic female newborn of 21q22.3 deletion with severe stenosis of the aortic valve and ascending aorta, mitral valve atresia, and hypoplastic left ventricle, who died of cardiopulmonary insufficiency after birth. A Colombian girl with 21q22.3 deletion and 7q35q36.3 duplication manifested an atrial septal defect, dilated coronary sinus, and interventricular communication [21]. The deleted location and size of 21q22.3 were similar with our case who had no cardiac anomaly.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Ciocca et al [20] reported a syndromic female newborn of 21q22.3 deletion with severe stenosis of the aortic valve and ascending aorta, mitral valve atresia, and hypoplastic left ventricle, who died of cardiopulmonary insufficiency after birth. A Colombian girl with 21q22.3 deletion and 7q35q36.3 duplication manifested an atrial septal defect, dilated coronary sinus, and interventricular communication [21]. The deleted location and size of 21q22.3 were similar with our case who had no cardiac anomaly.…”
Section: Discussionsupporting
confidence: 81%
“…Two (2/4) cases had downslanted palpebral fissures. Two (2/4) patients presented with upslanted palpebral fissures, which is similar to trisomy 21 syndrome [21,22]. One patient had small palpebral fissures [20].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Other less common chromosomal abnormalities reported co-occurring with an omphalocele include triploidy, 45, XO, 47, XXY, and 47, XXX [ 4 ]. A wide range of partial aneuploidy, including dup (3q), dup (11p) [ 10 ], inv (11), dup (1q), del (1q), dup (4q), dup (5p), dup (6q), del (9p), dup (15q) [ 11 ], dup (17q), dup (7q)/del (21q) [ 12 ], dup (3q)/del (9q) [ 13 ], Pallister-Killian syndrome with mosaic tetrasomy 12p and Miller-Dieker lissencephaly syndrome with deletion of 17p13.3, and uniparental disomy (UPD) such as UPD11 and UPD14, is also reported to be associated with omphalocele [ 4 , 10 , 11 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Duplicações parciais 7q foram classificadas em quatro grupos de acordo com a região cromossômica afetada. 43 Para o paciente detectado com a duplicação 8p24, haverá um acompanhamento neurológico para monitorar o desenvolvimento clínico, já que os genes associados à epilepsia estão localizados na região 8p24, e alterações nesta região podem ser responsáveis por convulsões tônicas, às vezes seguidas de convulsões clônicas generalizadas. Um dos genes envolvidos é o KCNQ3 (canais de potássio dependentes de voltagem, subfamília Q, membro 3).…”
Section: Grassi Et Al Deleção 22q112 Síndrome De Digeorgeunclassified